Pruning treatment: A possible method for improving the conservation status of a Ellisella paraplexauroides Stiasny, 1936 (Anthozoa, Alcyonacea) population in the Chafarinas Islands? - SANCHEZ-TOCINO, LUIS; DE LA LINDE RUBIO, ANTONIO; LIZANA ROSAS, M SOL; PÉREZ GUERRA, TEODORO; TIERNO DE FIGUEROA, JOSE MANUEL (Mediterranean Marine Science, 2018)
In the present paper, the results of a four-year conservation study on the giant gorgonian Ellisella paraplexauroides in the Chafarinas Islands are reported. This species, currently protected in Spain, is present as isolated colonies or as a low number of them, except in the Chafarinas Islands, where higher densities can be found below a depth of 20 m. Nevertheless, as revealed by a previous study, a great number of colonies are partially covered by epibionts or totally dead. As a first objective of the present work, seven transects were performed in 2013 and 2014 to evaluate the percentage of colonies affected in areas that had not been previously sampled. Approximately between 35% and 95% of the colonies had different degrees of epibiosis or were dead. In 2015, ten transects were performed to specifically locate young colonies smaller than 15 cm, which could be indicative of population regeneration by sexual reproduction. The high number of dead colonies as well as the colonies covered by epibionts, together with the inexistence of young colonies, indicated a progressive decline of the study population. The last aim of the study consisted of testing a restoration action by means of pruning the affected colonies between 2015 and 2016. The results of this restoration action showed a substantial improvement of the colonies (growth of branches, production of new branches and a general increase in the health status of the colonies). Our results recommend the employment of this technique for the future conservation of this species in the Chafarinas Islands. Nevertheless, this is a pilot study, and further experiments with a large number of samples should be performed to truly understand the significance of this technique.